BUSINESS DEVELOPMENT STRATEGY OF SIMPLE AND HEALTHY CLASS HOUSING INDUSTRY (CASE STUDY PT. MANDIRI PRATAMA PUTERA) - Hendriadi Hendriadi; Jusni Jusni; Erlina Pakki (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
This study aims to analyze the right strategy for PT. Mandiri Pratama Putera for the development of a simple and healthy class housing business. This type of research is development research through descriptive analysis with a qualitative approach. The study population was the directors and employees of PT. Mandiri Pratama Putra, amounting to 120 people. The research sample consisted of 16 people who were determined by the purposive sampling method. Collecting data in this study using participatory observation data, in-depth interviews, documentation data, and combining various data collection techniques in a study of a problem or triangulation. Data were analyzed using BMC analysis, Steeple, Five Forces, SWOT, EFE & IFE matrix, IE Matrix, SWOT Matrix, and QSPM. The results showed that the SWOT matrix analysis resulted in five alternative strategies, namely developing commercial products at low prices for low-income non-community segments, expansion to other areas for market development, making mortgage-free customer programs, making customer payment schemes that can be paid in installments every month to the company. without charging interest, market penetration by increasing the promotional cost budget. The results of the QSPM matrix analysis or the appropriate strategy decision-making stage implemented by PT. Mandiri Pratama Putra is to develop commercial products at low prices for low-income non-community segments or the general public who have incomes above the minimum wage, so they don't depend on selling subsidized low-cost housing products only.